Literature Study: Problems of Islamic Religious Education (PAI) Curriculum in Schools and Madrasah - Darain, A. Sa’dud; Hadi, Saiful (Prodi Bisnis Digital Universitas Pahlawan Tuanku Tambusai, 2026)
This literature study aims to comprehensively map the problems of implementing the Islamic Religious Education (PAI) curriculum in public schools and madrasas in Indonesia. This research uses a literature review approach by examining various scientific articles, policy reports, and relevant previous research results. The results of the study indicate that the challenges of implementing the PAI curriculum can be classified into three main levels: policy or curriculum design, classroom implementation, and evaluation and assessment systems. The research findings reveal differences in the pattern of problems between public schools and madrasas. In public schools, PAI tends to be marginalized due to limited time allocation and its position within the Independent Curriculum, resulting in shallow learning and solely cognitive-oriented learning. Meanwhile, madrasas face the complex problem of curriculum dualism between the national curriculum and the religious curriculum, which has the potential to burden students and reduce the depth of understanding of the material. On the other hand, both educational institutions face relatively similar challenges in implementation and evaluation aspects, such as the dominance of lecture methods, limited teacher pedagogical competence, difficulties in measuring affective and spiritual aspects, and weak integration of Islamic values ​​with the dynamics of the digital era and Society 5.0. This situation has hampered the effectiveness of Islamic Religious Education (PAI) in shaping the character, morals, and spirituality of students. Therefore, solutions are needed to develop a contextual, holistic, and systemic Islamic Religious Education (PAI) curriculum, taking into account the specific characteristics, needs, and challenges of each educational institution.